2022
DOI: 10.1002/cssc.202201801
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Key Factors in High Li+ Transference Number Composite Electrolytes for Solid Lithium Batteries

Abstract: Solid lithium batteries (SLBs) have received much attention due to their potential to achieve secondary batteries with high energy density and high safety. The solid electrolyte (SE) is believed to be the essential material for SLBs. Among the recent SEs, composite electrolytes have good interfacial compatibility and customizability, which have been broadly investigated as promising contenders for commercial SLBs. The high Li+ transference number (t Li+ ${{_{{\rm Li}{^{+}}}}}$ ) of composite electrolytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 161 publications
0
15
0
Order By: Relevance
“…According to the equation for calculation in the Section , the t Li+ of the LZEC composite electrolyte is approximately 0.71. The LZEC composite electrolyte contains many LLZTO nanoparticles, and the Lewis acid–base interactions between ceramics nanoparticles and mobile anions (PF 6 – ) are responsible for this high value, as previous research studies revealed. , The LZEC composite electrolyte with high t Li+ is expected to reduce polarization and facilitate uniform Li deposition, as it can alleviate the space charge layer at the electrolyte/electrode interface caused by free migration and accumulation of anions . More importantly, t Li+ represents the ratio of Li + to all mobile ions in composite electrolytes.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…According to the equation for calculation in the Section , the t Li+ of the LZEC composite electrolyte is approximately 0.71. The LZEC composite electrolyte contains many LLZTO nanoparticles, and the Lewis acid–base interactions between ceramics nanoparticles and mobile anions (PF 6 – ) are responsible for this high value, as previous research studies revealed. , The LZEC composite electrolyte with high t Li+ is expected to reduce polarization and facilitate uniform Li deposition, as it can alleviate the space charge layer at the electrolyte/electrode interface caused by free migration and accumulation of anions . More importantly, t Li+ represents the ratio of Li + to all mobile ions in composite electrolytes.…”
Section: Resultsmentioning
confidence: 98%
“…37,38 The LZEC composite electrolyte with high t Li+ is expected to reduce polarization and facilitate uniform Li deposition, as it can alleviate the space charge layer at the electrolyte/electrode interface caused by free migration and accumulation of anions. 46 More importantly, t Li+ represents the ratio of Li + to all mobile ions in composite electrolytes. So high t Li+ further demonstrates the superior ability of the LZEC composite electrolyte in conducting Li + , which may help to improve the rate performance of batteries.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Moreover, charge transfer, that is, electrons or ions, occurs at the solid-solid contact point between the SE and electrodes due to electrochemical reactions, such as Limetal deposition. [14,108,109] Consequently, mechanical alteration happens along the electrochemical reaction, leading to local lattice deformation of the SEs. [110] The extension of such alteration is normally restricted to the very surface layers of solid materials, triggering the local stress.…”
Section: Three-dimensional Stress Mapping By Raman Spectroscopymentioning
confidence: 99%
“…Therefore, long-term cycling will lead to lithium dendrite growth at the solid electrolyte grain boundaries and cause electrolyte failure and short-circuit the battery. The most direct way to solve wettability is to use artificial SEI layers or alloys of lithium metal with different metal elements , or composites with polymers to the solid composite electrolyte to change the mechanical properties of the electrolyte. Most of the artificial SEI layers are modified with Li 3 N, LiCl, LiF, , and other materials for interface layer modification, which improves the wettability between the electrolyte and lithium metal layer. The alloy part is quite broad.…”
Section: Introductionmentioning
confidence: 99%